Genetic parameters of calving interval in Nellore Cattler - Cardellino, Ricardo Alberto; Pons, Sérgio Brasil (Pesquisa Agropecuaria Brasileira, 2014)
Calving intervals were analyzed in two Nellore herds in Paraná (Brazil). Herd A had 165 observations (85 cows, 1976-78), and herd B 472 observations (161 cows, 1970-78). Intervals were described by linear models which included the effects of cow, year and season of birth (first calf), and age of dam in herd A; cow, sex of calf (second calf), month and year of birth (first calf) and age of dam, in herd B. Mean calving intervals were 477 ± 7.43 days for herd A, and 533 ± 7.64 for herd B. The interaction year x season was the only significant effect in herd A. In herd B the effects of cow, year, sex x year interaction and age of cow were significant. Repeatability estimates were 0.05 ± 0.12 for herd A, and 0.10 ± 0.03 for herd B. Both values are considered very low. Heritabilities of calving interval, most probable producing ability and maternal index (which includes weaning ratios and calving intervals) were estimated from 279 cow records (1962-76) in herd B. The values obtained were low, 0.05, 0.03 and 0.08. Selection will result in little genetic progress, but the inclusion of these traits in an improvement program seems justified as a diagnose tool.